Child protection involvement of children of mothers with intellectual disability. (April 2022) - Lima, Fernando; O'Donnell, Melissa; Bourke, Jenny; Wolff, Brittany; Gibberd, Alison; Llewellyn, Gwynnyth; Leonard, Helen
Abstract: Background: Children born to parents with intellectual disability (ID) have been shown as disproportionally represented in child protection services however with limited population-based research. Objectives: To investigate child protection involvement for children born to mothers with ID in Western Australia using linked administrative data. Participants and setting: A cohort of 1106 children born to a mother with ID and a comparison group of 9796 children of mothers without ID were identified in Western Australia. Methods: Cox regression analyses stratified by maternal Aboriginal status were conducted to investigate risk of child involvement with child protection services and care placement. Interaction with child age, intellectual disability status, and maternal mental health and substance use was investigated. Results: Children born to a mother with ID were both at higher risk of having contact with child protection services (HR: 4.35 (3.70–5.12)) and placement in out-of-home care (HR: 6.21 (4.73–8.17)). For non-Aboriginal children, the risks of child protection involvement and placement for those born to mothers with ID were 7 times and 12 times higher than those of mothers without ID. The risk was lower for Aboriginal children, at 1.8 and 1.9 times, respectively. Infants born to mothers with ID were at higher risk of child protection involvement compared to other age groups. Maternal mental health and substance use moderated the increased risk. Conclusions: Intellectual disability alone is not sufficient justification for removal of children from their parents. The challenge for family services is ensuring that resources are adequate to meet the family's needs. Highlights: This is a population-based linked data study enabling a large representative sample. Children of mothers with ID had 6 times higher risk of child protection involvement. Maternal mental health and substance use contacts moderated the increased risk.